Implementasi senam kaki mandiri dalam managemen nyeri diabetes (Gerakan Lansia Tangguh) - Yuli Susanti; Arista Adityasari Putri (JOURNAL of Public Health Concerns, 2026)
Background: Diabetes Mellitus (DM) is a chronic disease whose prevalence continues to increase globally, including in Indonesia. Impaired glucose regulation due to abnormalities in insulin secretion and function leads to increased blood glucose levels, potentially leading to various metabolic complications. At the national and regional levels, the number of DM sufferers continues to increase annually, including in Central Java Province, which shows a significant upward trend. One of the most common complications experienced by DM sufferers, especially in the elderly, is diabetic neuropathy. The prevalence of diabetic neuropathy in type 2 DM reaches more than 50%, making it a major cause of decreased quality of life in the elderly and a risk factor for diabetic ulcers. Karang Anyar Regency also reports a high number of type 2 DM sufferers accessing health services, thus increasing the risk of neuropathy. Management of diabetic neuropathy relies not only on pharmacological therapy but also non-pharmacological interventions. One intervention that has been proven effective and easy for the elderly to perform is diabetic foot exercises. This community service activity was conducted in Karang Anyar District by the Ahad Pagi community. The goal was to provide foot health education and facilitate the practice of diabetic foot exercises to reduce neuropathic pain, improve blood circulation, and support the independence of older adults in maintaining lower extremity health. Purpose: To provide education and support for diabetes management in older adults through independent foot exercises to address joint pain. Method: This community service was conducted through an initial survey by the team to all organizing committees of the Sunday Morning Study with PCM Karang Anyar Regency. The target of this activity was the management of diabetes in the elderly by implementing foot exercises. The activity with the theme "Resilient Elderly Movement" involved participants from the Sunday Morning Study Assembly of PCM Karang Anyar Regency. More than 70% of the participants who attended were elderly groups with a history of chronic diseases such as pain and diabetes mellitus as well as joint pain. The simulation activity was assisted by videos and presentations regarding the correct management of applying ginger wraps and foot exercises. Evaluation was carried out through observation and interviews to see the improvement in the elderly's ability to perform ginger wraps and foot exercises independently. Results: Participants in this activity were very enthusiastic about participating in the education, and there was a question-and-answer session covering diabetes complaints and blood sugar management. This finding confirms the high demand for diabetes education and ginger wrap therapy for joint pain among the elderly community. The implementation of the foot exercise activity, which included a demonstration of foot exercises, was very successful. Ten participants participated in the live demonstration using a rope for the demonstration. Furthermore, using ginger wrap therapy to reduce joint pain in the elderly allowed participants to directly experience the benefits of foot exercises, including reducing ankle pain due to neuropathy, a complication of diabetes, and ginger wrap therapy for reducing joint pain. Conclusion: Community service activities with a community approach are highly effective in improving the ability of older adults to maintain physical and mental health. Activities through education and demonstrations have a positive impact on strengthening awareness among older adults about healthy and active living, thus benefiting the community. Suggestion: Health education and foot exercise demonstrations are expected to be conducted regularly so that older adults can maintain knowledge and practice consistent management of diabetes and neuropathic pain. Integration into the Elderly Community Program, including foot exercises, can be included as a regular program during religious study groups or community meetings as an easy and affordable way to maintain the health of the feet of people with diabetes. Keywords: Diabetes mellitus; Elderly; Foot exercises; Joint pain; Topical ginger compress therapy Pendahuluan: Diabetes Mellitus (DM) merupakan penyakit kronis yang prevalensinya terus meningkat secara global, termasuk di Indonesia. Gangguan regulasi glukosa akibat kelainan sekresi maupun kerja insulin menyebabkan peningkatan kadar glukosa darah yang berpotensi menimbulkan berbagai komplikasi metabolik. Di tingkat nasional dan daerah, peningkatan jumlah penderita DM terus terjadi setiap tahunnya, termasuk di Provinsi Jawa Tengah yang menunjukkan tren kenaikan signifikan. Salah satu komplikasi yang paling banyak dialami penyandang DM, khususnya pada kelompok lansia, adalah neuropati diabetik. Prevalensi neuropati diabetik pada DM tipe 2 mencapai lebih dari 50%, sehingga menjadi penyebab utama penurunan kualitas hidup lansia dan menjadi faktor risiko terjadinya ulkus diabetik. Kabupaten Karanganyar juga melaporkan tingginya jumlah penderita DM tipe 2 yang mengakses layanan kesehatan, sehingga risiko terjadinya neuropati semakin besar. Penanganan neuropati diabetik tidak hanya mengandalkan terapi farmakologis, tetapi juga intervensi nonfarmakologis. Salah satu intervensi yang terbukti efektif dan mudah dilakukan lansia adalah senam kaki diabetik. Kegiatan pengabdian masyarakat ini dilaksanakan di Kecamatan Karanganyar pada komunitas Ahad Pagi dengan tujuan memberikan edukasi kesehatan kaki serta memfasilitasi praktik senam kaki diabetik guna mengurangi nyeri neuropati, meningkatkan sirkulasi darah, dan mendukung kemandirian lansia dalam menjaga kesehatan ekstremitas bawah. Tujuan: Memberikan edukasi dan pendampingan pengelolaan diabetes pada lansia melalui senam kaki mandiri dalam upaya menangani nyeri neuropati serta pemberian balut jahe untuk mengurangi nyeri sendi. Metode: Pengabdian masyarakat ini dilakukan dengan survei awal oleh tim ke semua panitia penyelenggara Kajian Ahad Pagi dengan PCM Kabupaten Karanganyar. Sasaran dalam kegiatan ini, adalah pengelolaan diabetes pada lansia dengan menerapkan senam kaki. Kegiatan dengan tema “Gerakan Lansia Tangguh” melibatkan peserta dari Majelis Pengajian Ahad Pagi PCM Kabupaten Karanganyar. Lebih dari 70% peserta yang hadir adalah kelompok lanjut usia yang memiliki riwayat penyakit kronik seperti nyeri dan diabetes mellitus serta nyeri sendi. Kegiatan simulasi dibantu dengan video dan presentasi mengenai tatalaksana menerapkan balut jahe dan senam kaki yang benar. Evaluasi dilakukan dengan observasi dan wawancara untuk melihat peningkatan kemampuan lansia dalam melakukan balut jahe dan senam kaki secara mandiri. Hasil: Peserta dalam kegiatan ini sangat antusias dalam mengikuti edukasi dan ada sesi tanya-jawab untuk sekitar keluhan penyakit diabetes dan pengelolaan kadar gula darah. Temuan ini merupakan konfirmasi dari kebutuhan dari komunitas lansia sangat tinggi tentang edukasi diabetes dan terapi balut jahe untuk nyeri sendi. Implementasi dari kegiatan senam kaki berupa demonastrasi senam kaki sangat baik. Sebanyak 10 peserta yang mewakili untuk pelaksanaan demonstrasi senam kaki langsung dengan bahan demonstrasi menggunakan korang untuk senam kaki. Dan terapi balut jahe untuk mengurangi nyeri di sendi pada lansia,  peserta dapat merasakan langsung manfaat dari senam kaki yaitu dapat mengurangi rasa nyeri di pergelangan kaki akibat neuropati komplikasi dari diabetes dan terapi balut jahe untuk mengurangi nyeri sendi. Simpulan: Kegiatan pengabdian masyarakat dengan pendekatan komunitas sangat efektif meningkatkan kemampuan lansia dalam menjaga kesehatan jasmani dan rohani. Kegiatan melalui edukasi dan pendampingan demonstrasi memberikan dampak positif dalam membangun penguatan kesadaran lansia untuk hidup sehat dan aktif sehingga bermanfaat bagi komunitas. Saran: Diharapkan edukasi kesehatan dan demonstrasi senam kaki perlu dilakukan secara berkala agar lansia dapat mempertahankan pengetahuan dan konsistensi dalam praktik manajemen diabetes dan nyeri neuropati. Integrasi dalam Program Komunitas Lansia yaitu senam kaki dapat dimasukkan sebagai program rutin dalam kegiatan pengajian atau pertemuan komunitas sebagai upaya mudah dan murah dalam menjaga kesehatan kaki penderita diabetes.